Pattern of drug therapy problems and interventions in ambulatory patients receiving antiretroviral therapy in Nigeria - Ojeh VB; Naima N; Abah IO; Falang KD; Lucy O; London I; Dady C; Agaba P; Agbaji O (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Objectives: We describe the frequency and types of drug therapy problems (DTPs), and interventions carried out to resolve them, among a cohort of HIV- infected patients on ART in Jos, Nigeria. Methods: A prospective pharmacists' intervention study was conducted between January and August 2012 at the outpatient HIV clinic of the Jos University Teaching Hospital (JUTH). Pharmacists identified DTPs and made recommendations to resolve them. The main outcome measures were number of DTPs encountered, interventions proposed and acceptance rate of recommendations. Results: A total of 42,416 prescriptions were dispensed to 9339 patients during the eight months study. A total of 420 interventions (Intervention rate of 1 per 100 prescriptions) were made to resolve DTPs in 401 (4.3%) patients with a mean age of 41 (SD=10) years, and made up of 73% females. DTPs encountered were drug omission (n=89, 21.2%), unnecessary drug (n=55, 13.1%) and wrong drug indication (n=55, 13.1%). Recommendations offered included; Addition of another drug to the therapy (n=87, 20.7%), rectification of incomplete prescriptions (n=85, 20.2%), change of drug or dosage (n=67, 16.0%), and discontinuation of the offending drug (n=59, 14.0%). A total of 389 (93%) out of 420 of the recommendations were accepted. In all, 50.4% (212) of the problematic prescriptions were changed and dispensed, 22.2% (89) were clarified and dispensed, while wrong identities were corrected in 11.7% (49). However, 7.5% (30) prescriptions were dispensed as prescribed, 5.2% (21) were not dispensed, and 3% (12) were unresolved. Conclusion: Our findings suggest that pharmacists-initiated interventions can ameliorate DTPs in patients receiving ART given the high intervention acceptance rate recorded. The implication of this finding is that pharmacists with requisite training in HIV pharmacotherapy are an excellent resource in detecting and minimizing the effect of antiretroviral drug-related errors.